CORRELATION OF THE FLAT FOOT AND THE SEVERITY OF SCOLIOSIS IN ELDERLY PATIENTS AT PHC HOSPITAL SURABAYA - Arief, Teuku; Ricardo, Henry; Tahalele, Paul L; Huang, Velinda (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Background: The main symptoms of Scoliosis are changes in body posture, such as unlevel shoulders, rib prominence, or waistline asymmetry. Some previous studies have shown major role of feet a in supporting the body weight support and providing dynamic balance in gait function. Moreover, flat foot (pes planus) may cause lower limb rotation and low back pain possibly due to altered postural reactions and subsequent compensatory patterns between the spine and lower extremitiesObjective: To explain the correlation between the incidence of pes planus and the severity of scoliosis in elderly patients (≥60 y.o) at PHC Surabaya Hospital.Method: This research is an analytical research using a cross sectional study, used probability sampling with purposive sampling. The minimum number of samples required in this research was calculated using the Lemeshow formula, resulting in 69 samples. Data were collected in the form of primary data (Clarke's angle measurement results in the medial longitudinal arch [MLA]) and secondary data (medical records) from 69 patients with a history of scoliosis (using the Cobb Angle Criteria) at PHC Surabaya Hospital in August – October 2023 by Specialist in Orthopedics and Traumatology. Then tested with the Spearman Correlation test using the Statistical Package for the Social Sciences (SPSS) version 29.Results: Of the 69 patients diagnosed with flat foot (pes planus) studied, it was found that 57 patients (82.6%) had scoliosis, but based on the results of statistical analysis of the two variables these were not significantly correlated (p = 0.932).Conclusion: There were no significant results regarding the correlation between the incidence of flat foot (pes planus) and the severity of scoliosis at PHC Surabaya Hospital. This is related to the inclusion and exclusion criteria set by researchers, such as age, BMI, and past medical history.